Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18): Proceedings of the International conference, 1–5 October 2018, Tomsk, Russia; AIP Conference Proceedings - Panin V. E. Viktor Evgenyevich; Psakhie S. G. Sergey Grigorievich; Fomin V. M. (2018, 2018)
Title screen